Does ESG Investing Strategy Really Mattern For Youth? A Study From Indonesia Youth Behavior - Agni Satria Perdana; Fitri Santi (Journal of Studies in Academic, Humanities, Research, and Innovation, 2025)
This study examines the relationship between individual moral orientation and investment decision-making among young investors in Indonesia within the framework of Environmental, Social, and Governance (ESG) investing. The research is motivated by the rapid growth of youth participation in Indonesia’s capital market and the increasing relevance of sustainable finance practices in emerging economies. Employing an experimental research design, data were collected from 110 university students with prior knowledge of financial management and investment, of which 100 met the validity criteria and were included in the analysis. Participants were randomly assigned into experimental and control groups, and further categorized into high- and low-morality cohorts based on a modified moral character scale (Furr et al., 2022). The experimental group was exposed to moral scenarios depicting ethical and unethical corporate practices, whereas the control group was presented with conventional financial return information. Statistical analyses using the Wilcoxon and Spearman correlation tests revealed significant behavioral differences between groups. Participants with higher moral orientations demonstrated stronger ethical sensitivity by divesting entirely from companies exhibiting immoral conduct and reallocating their portfolios toward firms with higher moral and ESG standards. In contrast, participants with lower moral orientations prioritized financial returns over ethical considerations. The correlation results (r = –0.425, p < 0.05) confirmed a negative association between moral level and investment in immoral companies, supporting both hypotheses that morality influences investment decisions and that moral companies are valued more highly by investors. The findings underscore the pivotal role of moral cognition in shaping investment behavior and provide empirical evidence that ethical awareness among young investors contributes to the advancement of sustainable and socially responsible financial ecosystems in developing market